1004 Smith-<Magenis Syndrome (SMS) Circadian Abnormalities And Biological Rhythms. (27th May 2020) - Brooks, J; Gibson, M; Kite, K; Czeisler, E; Fisher, M; Xiao, C; Polymeropoulos, C; Polymeropoulos, M
Abstract: Introduction: SMS is a rare neurodevelopmental disorder that manifests with craniofacial abnormalities, behavioral disturbances, and a severe sleep disorder. It has been reported that many SMS patients have an inverted melatonin secretion pattern (peaking during the daytime) although a small minority have near normal patterns. The goal of this study was to better characterize the intra- and inter-patient variability of melatonin secretion patterns and investigate a potential relationship with sleep behavior in SMS patients. Methods: In this observational study, sleep behaviors of patients (N=8, 1 female, ages: 7 - 35) with SMS were characterized through caretaker surveys. On 3 separate occasions, patients had hourly serum melatonin levels sampled for 36 hours. From these data, peak serum melatonin concentration and time of peak concentration were determined. Inter- and intra-patient variability was characterized by zero lag correlation of the melatonin concentration timeseries across and within patients, respectively. The relationship between peak melatonin concentration, peak time, and sleep latency was analyzed by a generalized linear model, GLM. Results: Peak melatonin concentrations varied across SMS patients with a range of 3.55pg/ml - 49.65pg/ml (mean 14.18 ± 15.19pg/ml). Time of peak melatonin concentrations ranged from 0400h-2100h (mean 1422 ± 6h). Correlation coefficients characterizing intra-patient variability ranged from -0.0098 to 0.89 (mean 0.55 ± 0.2533). Correlation coefficients characterizing inter-patient variability ranged from -0.75 to 0.79 (mean of 0.18 ± 0.52). Sleep latency ranged from 8.4min - 36.35min (mean of 21.99 ± 9.77 min). GLM analysis demonstrated a significant, positive effect of peak time with sleep latency (p=0.022). Conclusion: Consistent with previous findings, our study confirms that SMS patients have abnormal circadian rhythms. Our work extends this body of literature by demonstrating a significant degree of inter-patient variability with relatively stable intra-patient variability. Preliminary evidence suggests that the timing of melatonin peak may be related to sleep onset latency. Support: This work was supported by Vanda Pharmaceuticals Inc.